Analisis Beban Kerja Dokter di Klinik Pratama Ubhara Jaya dengan Metode Full Time Equivalent - Arya Hadid Pangestu; Alan Setiyawan; Teuku Alfiansyah; Hedi Sutiawan; Dwi Aliega Fauzi; Nurli Dian Stefani Sianturi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyse the workload of doctors at Ubhara Jaya Primary Clinic in order to improve the efficiency and quality of medical services. Effective human resource management, particularly in managing doctors' workload, is essential to provide fast, precise, and quality health services. This study uses the Full Time Equivalent (FTE) method to measure and analyse doctor workload. Interviews and direct observation were used to get primary data, while secondary data was collected from relevant documents such as doctors' work schedules, monthly reports, and medical records. The research method used is descriptive with a quantitative approach, as well as literature review as a theoretical basis. The overall results of the various activities carried out by doctors at the Ubhara Jaya Primary Clinic show that the FTE index value is below the normal limit, these results indicate the need for additional workload and do not require additional labour for each activity performed.